Mammary mucinous cystadenocarcinoma with long-term follow-up: molecular information and literature review - Ting Lei; Yong Qiang Shi; Tong Bing Chen (BMC, 2023)
Abstract Background Mucinous cystadenocarcinoma (MCA) is a very rare form of breast cancer that was first described in 1998. Only 33 cases of primary MCA, including our present case, have been reported thus far. As a consequence, its molecular features, prognosis and treatment regimen are poorly known. Here, we describe a less common presentation of MCA, detail its molecular features, discuss the major differential diagnosis, and provide a brief review of the literature. Case presentation A 59-year-old woman presented with a breast lump in which mammography showed a well-defined nodule. Core needle biopsy (CNB) revealed several lesions lined by tall columnar cells with stratification and abundant mucinous secretion; excision was recommended for final diagnosis. The resected specimens showed cavities of different sizes without surrounding myoepithelial cells. The cavities were rich in mucus, and the nuclei were located at the base of the cells, containing intracellular mucus. Immunohistochemical analysis revealed that it was triple-negative breast cancer (TNBC). Next-generation sequencing (NGS) revealed pathogenic mutations in the PIK3CA, KRAS, MAP2K4, RB1, KDR, PKHD1, TERT, and TP53 genes. A diagnosis of MCA was rendered. The patient has been followed up for 108 months to date and showed no signs of recurrence or metastasis. Conclusion Our study presents the gene profile of an MCA case with no recurrence or metastatic tendency after 108 months of follow-up, and a review of the literature helps us better understand the clinical, pathologic, and molecular features of this tumor.